Prevalence and determinants of left ventricular hypertrophy in hypertensive patients at a primary care clinic - Chia, Y.C.; Ching, S.M.; Wan Azman, W.A. (Academy of Family Physicians of Malaysia, 2012)
Left ventricular hypertrophy (LVH) has prognostic significance on cardiovascular mortality and morbidity. However, echocardiography screening for LVH is not routinely done for hypertensive patients in a primary care setting. Thus, this quantitative study aims to determine the prevalence and factors associated with LVH in hypertensive patients at a primary care setting. This was a cross sectional study of 359 consecutive patients with uncomplicated essential hypertension attending a hospital-based clinic in Malaysia. All subjects underwent an echocardiography test. LVH occur when the left ventricular posterior wall thickness together with inter-ventricular septal thickness is ≥11 mm. It was found that 24% patients fulfilled the criteria for LVH. The mean age of the study population was 59.2±7.7 years; mean duration of hypertension was 9.7±7.5 years; and mean blood pressure was 136.5/81.5 (±13.7/7.7) mmHg. Using multiple logistic regression analysis, patients who were obese [odds ratio (OR) 8.34, 95% confidence interval (CI) 3.14, 22.22] and male gender (OR 1.96, 95% CI 1.08, 3.16) had significant positive association with LVH. LVH was found in approximately one fourth of the hypertensive patients at a hospital-based primary care setting. There was a significant positive association between LVH and obesity and being male. Guidelines for enhancing use of echocardiography in detecting LVH may be needed.